Non-Catalytic Biodiesel Synthesis from Kemiri Sunan (Reutealis trisperma) in Semi-Batch Bubble Column Reactor - J. Joelianingsih; Faisal Ramadhan Nur; Melani Eka Saputri; Is Sulistyati Purwaningsih (Dept. of Chemical Engineering, Diponegoro University, 2021)
The Bubble Column Reactor (BCR) is intensive equipment used as a multiphase contactor and reactor in the chemical, biochemical, and petrochemical industries. BCR has some advantages include high mass and heat transfer rates, compactness, and low operating and maintenance costs. In this research, BCR was applied to produce biodiesel from Kemiri Sunan (Reutealis trisperma) Oil through non-catalytic and simultaneous esterification and transesterification reactions. Kemiri Sunan Oil was fed in the reactor and heated to a specific temperature. During the heating process, nitrogen gas was flowed to prevent oxidation. Liquid methanol flowed at some various flow rates through a vaporizer and superheater so that it has flowed into the reactor in the form of saturated steam (1 atm, 240 ºC). Experiments with variations in the methanol flow rate were carried out at a reaction temperature of 250 ºC, while experiments with various temperatures were carried out at a methanol flow rate of 2.5 mL/min. The best conditions were obtained at a flow rate of 2.5 mL min with a reaction temperature of 290 ºC. The production rate was 3.47 g/min with an acid number of 0.69 mg KOH/gr sample, and FAME content was 78.2% wt. These results indicate the simultaneous esterification and transesterification reaction in one reactor.